Decision Procedure for Synchronous Kleene Algebra - Horta, Luís Pedro Arrojado da (2018)
Kleene Algebra (KA) is an algebraic system that has many applications both in mathematics and computer science. It was named after Stephen Cole Kleene who extensively studied regular expressions and finite automata [Kle56]. Moreover it is often used to reason about programs, as it can represent sequential composition, choice and finite iteration. Furthermore, the need to reason about actions which can be executed concurrently, spawned SKA. SKA is an extension of KA introduced by Cristian Prisacariu in [Pri10] that adopts a notion of concurrent actions. Laguange equivalence is an imperishable problem in computer science. In this thesis we present the reader with a detailed explanation of a decision procedure for SKA terms and an OCaml implementation of said procedure as well.